2017
DOI: 10.3168/jds.2016-11450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major yeasts isolated from high moisture corn and corn silages in the United States using genetic and biochemical methods

Abstract: The objective of this study was to identify species of yeasts in samples of high moisture corn (HMC) and corn silage (CS) collected from farms throughout the United States. Samples were plated and colonies were isolated for identification using DNA analysis. Randomly selected colonies were also identified by fatty acid methyl esters (FAME) and by physiological substrate profiling (ID 32C). For CS, Candida ethanolica, Saccharomyces bulderi, Pichia anomala, Kazachstania unispora, and Saccharomyces cerevisiae wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 36 publications
3
25
0
1
Order By: Relevance
“…Considering the fact that cattle and other animals have been continuously exposed to different environmental Saccharomyces over millions of years, and the generalized belief that the presence of Saccharomyces in the gut only reflects dietary contamination (see above), an explanation of why Saccharomyces never became indigenous is necessary. The load of Saccharomyces and other microorganisms in animal feed is a very interesting topic but unfortunately has not been well studied (Santos et al, 2017). We hypothesize that the Saccharomyces present in the feed may have never become adapted to the gut because every time the animal feeds, it feeds with different types of Saccharomyces; therefore by the time one strain attempts to colonize, it gets removed (out-competed) by other strains.…”
Section: In Vivo Mode Of Action Of Saccharomyces In Livestockmentioning
confidence: 99%
“…Considering the fact that cattle and other animals have been continuously exposed to different environmental Saccharomyces over millions of years, and the generalized belief that the presence of Saccharomyces in the gut only reflects dietary contamination (see above), an explanation of why Saccharomyces never became indigenous is necessary. The load of Saccharomyces and other microorganisms in animal feed is a very interesting topic but unfortunately has not been well studied (Santos et al, 2017). We hypothesize that the Saccharomyces present in the feed may have never become adapted to the gut because every time the animal feeds, it feeds with different types of Saccharomyces; therefore by the time one strain attempts to colonize, it gets removed (out-competed) by other strains.…”
Section: In Vivo Mode Of Action Of Saccharomyces In Livestockmentioning
confidence: 99%
“…Kazachstania was the dominant yeast genus after four (7.0 to 16.6%) and eight (9.4 to 20.7%) days of fermentation, but subsequently decreased in abundance in all but the Control samples. Santos et al [48] studied the diversity of yeast populations in corn and high moisture corn silages. They reported that isolates obtained on malt agar plates showed that Candida, Saccharomyces, Pichia, and Kazachstania were the dominant genera.…”
Section: Fungal Succession During the Course Of The Incubation Periodmentioning
confidence: 99%
“…Sample #5 was identified as Candida guilliermondii by sequencing and sample #11 could not be identified at all. A recent study (Santos et al., ) compared DNA analysis, one automated method (API ® /ID32), and fatty acid methyl esters profile as methods for yeast identification. Despite the differences between the studies design, the authors also reported low agreement among methods, when investigating samples recovered from environmental sources.…”
Section: Resultsmentioning
confidence: 99%